Dans le sillage de la marine de guerre, pouvoir et Eglise en Guadeloupe (1940-1943) - Chathuant, Dominique (Bulletin de la Société d'Histoire de la Guadeloupe)

(untitled) (Société d'Histoire de la Guadeloupe, 1995)
Genoud, bishop in Guadeloupe from 1912 to 1945, became an unquestioning partisan of the new regime when, in 1940, Marshal Pétain established the government of the National Revolution. Bishop Gay become Genoud's coadjutor in 1943 ; he eventually succeeded him at the head of the diocese. He arrived in Guadeloupe a little after the joining of the island to De Gaulle ’s France. Because of Genoud's well-known unquestioning petainism one may wonder if Jean Gay did not owe his position to a religious purge. According to documents issued by the Minister’s office in charge of the colonies at that time, such a conclusion has to be disproved. In fact, Bishop Genoud was surrounded by government officials that the Vichy regime in Guadeloupe quickly got rid of. The latter opened negotiations with the highest religious authorities to flank Genoud with a coadjutor sympathetic to the National Revolution : Jean Gay. At the same time the regime continued to assure the bishops of its official aid. But the war delayed the new coadjutor’s trip. Ready to leave in the early months of 1943, the German and later the Italian authorities gave him permission to leave for Rome. He was then taken to Spain and Portugal. It is at that time that Admiral Robert, high commissioner to the French Caribbean, realized he had no alternative but to give up to obey Vichy. It appears that Gay was contacted in Lisbon by the Free French whose government was in Algiers. He had to continue his journey with the Allied Forces. Portuguese Guinea, Liberia, Brazil, the Guianas and Trinidad followed one another until the plane landed in Martinique. After a few hesitations, the Gaullist authorities accepted to let him go to Guadeloupe where he landed on August 10, 1943. But what were the real reasons for such an interest in a religious leader by the colonial authorities ? This was probably linked to the picture the ruling circles had of the Church, circles that considered the latter, rightly or wrongly, as a way to maintain power at a time when theology of liberation was unheard of.